[Rezension von: Herriott, Charlotte, Sexual History Evidence in Rape Trials: Is the Jury Out?] - Russell, Yvette (The British journal of criminology, 2024)
In sexual violence studies, empirical research on mock jurors in the United Kingdom continues to provide us with important insights into the way jurors mak